Investigation of Fibrous Materials for Low Frequency and High-Frequency Passive Noise Reduction using Transfer Matrix Method - Sreeja, R. (Journal of Scientific Research, 2022)
The concern about the adverse effects of noise pollution is enhancing day by day due to fast industrialization. Hence a wide variety of active and passive noise controllers made of natural and synthetic materials are widely used for various types of inevitable noise reduction. The different types of passive noise controllers fabricated using various techniques vary in their microstructure and surface morphology. In turn, they cause a difference in the noise-controlling mechanisms happening inside it, leading to its unique acoustic absorption characteristics. This article uses five different fibers of different fiber diameters to fabricate passive acoustic absorbers of different textures. The frequency response of their acoustic absorption coefficient is tested with the help of impedance tube apparatus using the transfer matrix method. Acoustic properties of coir fiber, basalt fiber, glass fiber, graphene fiber, and carbon fiber are investigated and compared. The present investigation focused on the influence of fiber diameter, the porosity, and the difference in the texture of these passive absorbers on the acoustic characteristics, frequency response of acoustic absorption coefficient, and the frequency corresponding to maximum absorption. The investigation also focuses on fabricating the passive absorbers for low-frequency noise reduction where only the active absorbers are available.